The dark side of play: play fighting as a substitute for real fighting in domestic pigs, Sus scrofa. (May 2021) - Cordoni, Giada; Gioia, Marika; Demuru, Elisa; Norscia, Ivan
Abstract : Play fighting can originate from different behavioural systems, including aggression and affiliation and can have a competitive and/or cooperative nature. Domestic pigs engage in vigorous play fighting that strongly resembles real fighting in motor patterns from their first days of life and heavier subjects usually win agonistic contests. Here we tested whether play fighting in piglets could be a substitute for real fighting and predicted that, if so: (1) play invitations would be more successful when not involving possibly dangerous body contact (Prediction 1); (2) piglets would preferentially play with similar-sized mates, easier to outcompete (Prediction 2); (3) play fighting and real fighting outcomes (winner/loser) and social networks would largely match (Prediction 3). We videorecorded three litters of preweaning piglets housed at the ethical farm Parva Domus (Turin, Italy) and analysed the play, aggression and suckling sessions. Sociomatrix and social network analyses were also used to compare play fighting and real fighting. Our findings confirmed all predictions, as they showed that piglets engaged in play fighting when the danger of being harmed was lowest (no-contact invitation patterns; Prediction 1) and their chance of winning was highest (similar weight players; Prediction 2). During the preweaning period, play fighting decreased as real fighting increased and just after suckling time declined, with piglets consistently winning/losing both playful and real fights and possessing comparable network centrality values in both play fighting and real fighting networks (Prediction 3). Although the mechanisms underlying the competitive nature of play fighting remain to be determined, this study provides evidence that it can be a harmless replacement for real fighting (possibly mediated by the oxytocin consumed via maternal milk). This study also points towards the more extreme hypothesis that play fighting is a different form of aggression that includes elements of play. Highlights: In piglets play fighting can function as a substitute for real fighting. Play fighting in piglets decreases right after the suckling time reduction. The same piglets occupy central positions in play and real fighting social network. Play fighting and real fighting outcomes (winner/loser) largely match.